Breast Units: unidades de diagnóstico e tratamento do câncer de mama - Vieira, René Aloísio da Costa; Matthes, Ângelo Gustavo Zucca; Uemura, Gilberto [UNESP] (My University, 2013)
The concept of a globalized world is everywhere. In mastology the idea of organizing network services, with high technological and quality protocol is coming true. The European Society of Mastology, in 1998, began the process of registration of Breast Units, aiming to determine minimum parameters related to high level for diagnosis and treatment of breast cancer, with minimum quality criteria, susceptible to certification, and quality programs. There are currently 137 full members, 26 certified, distributed in 44 countries, mostly in Europe. In Brazil there are six centers, with only four full members, but no center has the EUSOMA certificate, since the absence of organized mammography screening according to the European quality standard. Likewise, aiming the formation and refinement of programs of minimum attendance, the American College of Surgeons, in 2005, initiated the organization of the National Accreditation Program of Breast Centers. Nowadays there are 28 standard programs with re-certification process every three years. The 365 centers have minimum parameters of quality and they also use programs related to the different medial specialties involved. In Brazil, there are 74 centers registered on the Brazilian Society of Mastology, but there are no regular certifications. The network organization of Breast Units, evaluated according to the technological organization, associated with quality control programs, grouped by certification and re-certification process are the goals to be considered in which the great beneficiary will be the woman.

O conceito do mundo globalizado encontra-se por toda a parte. Na mastologia, a ideia de formação de rede de atendimento, associada a padrões tecnológicos e de alta qualidade, vem se solidificando. A Sociedade Europeia de Mastologia, em 1998, iniciou o processo de cadastramento de unidades mamá- rias, chamadas Breast Units, visando determinar parâmetros mínimos para as unidades de diagnóstico e tratamento do câncer de mama, com critérios de qualidade mínimos, passíveis de certificação, e programas de qualidade. Atualmente, são 137 membros completos, 26 certificados, distribuídos em 44 países, sendo a maioria na Europa. No Brasil, são seis centros, sendo apenas quatro plenos, não havendo nenhum centro com certificado, visto a ausência de rastreamento mamográfico organizado no padrão de qualidade europeu. Da mesma forma, visando a formação e aprimoramento de programas de atendimento mínimo, o Colégio Americano dos Cirurgiões iniciou, em 2005, a criação do National Accreditation Program of Breast Centers, sendo atualmente 28 programas padrão, com recertificação a cada 3 anos, em 365 centros, associados a programas de controle de qualidade regulamentados pelas especialidades envolvidas. No Brasil, existem 74 centros cadastrados na Sociedade Brasileira de Mastologia, porém não há certificações regulares. A formação de rede de unidades mamárias, escalonadas em função de sua complexidade tecnológica com programas de controle de qualidade, certificação e recertificação são metas que se devem considerar, nas quais a grande beneficiada será a mulher.
Breast Units: units for diagnosis and breast cancer treatment
Keywords: Breast neoplasms; Mammography; Diagnosis; Treatment; Quality control; Neoplasias da mama; Mamografia; Diagnóstico; Tratamento; Controle de qualidade